EFEKTIFITAS PEMBELARAN TAHFIZHIL AL-QURAN DALAM MENINGKATKAN HAFALAN SANTRI DI ISLAMIC CENTRE SUMATERA UTARA - M. Hanafiah Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2017)
The purpose of this research is: (1) to see the implementation of learning tahfiz Al-Quran at the Islamic Center of North Sumatra; (2) to identify the level of ability of memorizing the Quran Naat on the Islamic Center of North Sumatra. The approach was conducted in this study is a qualitative approach, the acquisition of this research data dug through the process of observation (observing) the field, carrying out interviews on various related parties, and study documents related. The analysis of the data done by the collection of data, data presentation, data reduction, and the withdrawal of the conclusion. The results of this research are; (1) the learning process tahfizh Al-Quran Islamic Center Foundation in North Sumatra, where is planning or rules that have been set well done Madrasah parties, ranging from the early riser, memorizing the Quran ready dawn, following the learning process, until at the end of which time the specified break time. Learning methods Tahfizh Al-Quran also remain selective and restrictive, for example, every time memorizing students wrong or ' severe ' bogged down as much as 3 times, it will be allowed to take the time to return other tasmi '; (2) the process of learning in the Foundation of the Islamic centre is effective one is by reviewing the achievement results of memorizing the santri. In this case, the students had a good achievement level, where students could memorize more than the juz 3 in one semester or about 0.5 sheets per day. Thus, through a process of review and following his findings, the visibility that the tahfizh Al-Quran learning in the Foundation of the Islamic Centre is effective.